2017
DOI: 10.1186/s12872-017-0621-3
|View full text |Cite
|
Sign up to set email alerts
|

Successful percutaneous coronary intervention in the setting of an aberrant left coronary artery arising from the right coronary cusp in a patient with acute coronary syndrome: a case report

Abstract: BackgroundAn aberrant origin of the left coronary artery (LCA) from the right coronary cusp (RCC) is an extremely rare congenital anomaly. We here report on successful percutaneous coronary intervention (PCI) in a patient presenting with acute coronary syndrome and an aberrant origin of the LCA from the RCC.Case presentationA 50-year-old man presented at our emergency department with recurrent resting chest pain. Following unsuccessful attempts at visualizing the left coronary artery using Judkins left and Amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…To our knowledge, this is the first report of this anomaly with a cardiogenic shock related to a 100% occlusive lesion in the anomalous LCA successfully treated with percutaneous intervention (PCI). One previous case from Korea has described the same anomaly with an acute coronary syndrome by an up-to-90% occlusive lesion in the proximal LAD [8]. Shah et al reported a similar case which was successfully treated with percutaneous intervention [9].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first report of this anomaly with a cardiogenic shock related to a 100% occlusive lesion in the anomalous LCA successfully treated with percutaneous intervention (PCI). One previous case from Korea has described the same anomaly with an acute coronary syndrome by an up-to-90% occlusive lesion in the proximal LAD [8]. Shah et al reported a similar case which was successfully treated with percutaneous intervention [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, a series of cases have been described where the heterogeneity of therapeutic options is observed for patients with anomaly of the LCA originating in the RCS or directly from the RCA associated with obstructive coronary disease, for example, patients who had surgical resolution in the cases reported by Shtembari et al and Coceani et al 7,8 Although there are other cases that required PCI, or that were only managed with pharmacological treatment and cardiological follow-up. 4,[9][10][11]…”
Section: Discussionmentioning
confidence: 99%
“…In a case report by Gac et al, they opted for medical therapy amid interventional and surgical treatment considering the nature of the pathophysiology and comorbidities of their patient despite considering CABG as a potential option [ 8 ]. Percutaneous coronary intervention (PCI) and surgical intervention as effective treatment options are well illustrated by Lee and Park [ 9 ], Khalighi et al [ 2 ], Narayanan et al [ 3 ], and Baik et al [ 10 ].…”
Section: Discussionmentioning
confidence: 99%